Diagnosis and management of de novo inflammatory bowel disease after solid organ transplantation in the era of biologic therapy: a case series - Johnson, Willie Mohammed; Vaughn, Byron P.; Lim, Nicholas (Frontiers in Transplantation, 2025)
IntroductionThe clinical characteristics of de novo inflammatory bowel disease (dnIBD) diagnosed after solid organ transplant (SOT) are not well-described, particularly since the advent of biologic therapy for treatment of IBD.MethodsWe conducted a single-center, retrospective review of SOT recipients between 2010 and 2022 at the University of Minnesota Medical Center who were diagnosed with IBD after transplant.ResultsOf 89 patients at our center with IBD and a history of SOT, five (5.6%) patients were diagnosed with IBD post-transplant (three liver, one kidney, and one simultaneous liver and kidney): three patients were female and four were Caucasian. Mean age at transplant and IBD diagnosis were 46.7 and 49.4 years respectively. Indication for transplant were alcohol-related cirrhosis (n = 2), idiopathic fulminant hepatic failure (n = 1), metabolic dysfunction-associated steatotic liver disease (n = 1), and IgA nephropathy (n = 1). Four patients were diagnosed with ulcerative colitis (UC) and one with Crohn's disease (CD). Three patients (all with UC) required escalation to a biologic therapy. Four patients were in clinical remission from IBD at last follow-up, one patient required IBD surgery, while there was no rejection and no deaths following IBD diagnosis.ConclusiondnIBD post-SOT is uncommon, while newer IBD therapies may be safe and effective. Further study is required to better understand the natural history and IBD outcomes of this population relative to non-SOT patients.